Competence Model of Coal Mining Enterprise Managers - Svyatoslav ZAKHAROV; Tatyana KORKINA; Igor BAEV (Communications of International Proceedings, 2020)
Relevance of the study is due to the need to improve competitiveness of coal mining enterprises operating in a global innovative economy. At the same time, the models of activity implemented by the management personnel of coal mining enterprises do not fully meet these conditions, which hinder the development of enterprises. To solve this problem, it is necessary to identify gaps in a leader activity structure and form a scientific and methodological base that allows them to be overcome. The purpose of the paper is to develop and substantiate a model for the activities of management personnel of a coal mining enterprise (CME), which ensures its competitiveness in a global innovative economy. The research methodology contains on competence-based and process-based approaches. To achieve the goal, methods of expert assessments, analysis, comparison, observation and synthesis were used. As the main object of research, middle managers of a coal mining enterprise were singled out. The developed model of competencies includes two interrelated areas: theoretical (ideas and knowledge) and practical (skills and abilities), which, in turn, are divided into three more types: global, innovative and economic competencies. Approbation of the developed model showed that the largest gaps and, consequently, the reserves for growth of the quality of managerial work are associated with such competencies as ability and skill of planning, organization and monitoring results of functioning and improving the object of management, as well as knowledge of advanced technical and technological solutions. With a relatively high rate of development of the personnel ideas and knowledge in the field of advanced technical, technological and organizational solutions there are low rates of abilities and planning skills development, organization and control of functioning results and improvement of the object control, which is due to the lack of effective mechanisms for involving personnel in production and management processes.
Keywords: Competence Model; Innovation; Globalization; Manager; Coal Mining Enterprise; Intellectual And Innovative Potential; Competitiveness.